Relationship of Weight Status, Physical Activity and Screen Time with Academic Achievement in Adolescents - Garcia-Hermoso, A (Elsevier Ltd, 2017)
Objective The aim of this study was to examine the relationship of weight status, physical activity and screen time with academic achievement in Chilean adolescents. Methods The present cross-sectional study included 395 adolescents. The International Obesity Task Force cut-off points were used to define the weight status. Physical activity was assessed using the Physical Activity Questionnaire for Adolescents and screen time was assessed using several questions about television, videogame and computer use. Academic achievement was measured using the mean of the grades obtained in mathematics and language subjects. Results In both genders, adolescents with obesity and excessive screen time earned worse grades compared to their non-obese peers and their peers that complied with screen time recommendations. The logistic regression analysis showed that adolescents with obesity, classified with medium–low physical activity and excessive screen time recommendations (excess ≥2 h/day) are less likely to obtain high academic achievement (boys: OR = 0.26; girls: OR = 0.23) compared to their non-obese peers, high levels of physical activity and those who comply with the current screen time recommendations. Similar results were observed in adolescents with obesity and classified with medium–low physical activity (boys: OR = 0.46; girls: OR = 0.33) or excessive screen time (boys: OR = 0.35; girls: OR = 0.36) compared to adolescents with high levels of physical activity and those who complied with the screen time recommendations, respectively. Conclusion This study shows that when combined, obesity, low–medium levels of physical activity and excessive screen time might be related to poor academic achievement. © 2015 Asia Oceania Association for the Study of Obesity